Novas variedades de laranjeiras Baías para a citricultura de mesa - Desiderio, Daniel Rodrigues (Universidade Federal de São Carlos, 2022)
Brazil is the world's largest producer of orange, destined for industry or fresh consumption. Encouraging the planting of table orange orchards can become a profitable activity in several regions of Brazil, but for this it is necessary to increase production and the quality of table citrus fruits. The objective of this work was to characterize new varieties of Bahia oranges, looking for new options that present better characteristics for the fresh fruit segment, with good coloring and organoleptic characteristics accepted by the market. The work carried out included twenty-two varieties of sweet orange trees (Citrus sinensis (L.) Osbeck) – Bahia type, grafted on Rangpur lime (Citrus limonia Osbeck), planted since 2015 at Centro de Citricultura Sylvio Moreira/IAC. The physical-chemical characteristics of the fruits (fruit mass, juice yield, total soluble solids, acidity and ratio) were analyzed to evaluate the maturation of the varieties throughout the 2019/2020 harvest, the vegetative development (crown volume) and productivity. On average, the varieties produced 37.5 t.ha-1, good productivity for five-year-old plants, under rainfed conditions. Six varieties of the evaluated Bays group were identified that fit as early maturing varieties (Navelina IAC 423, Washington Navel IAC 27, Navelina ISA 315, Baianinha Piracicaba IAC 41, Vale Del Cauca IAC 38 and Monte Parnazo IAC 20); eight are mid-season (Baia New Hall 3 MNH, Navelina ISA 315, Navelina SPA 12, Baianinha IAC 1417, New Hall Navel SRA 343, Baianinhas IAC 33, 22 and 37) and eight are late (Navelate, Baia Cabula IAC 25, Lane Late SPA 23, Robertson Navel IAC 39, Navelina IAC 423, Baia Valente IAC 28, Baianinha IAC 35 and Baianinha IAC 79). Producing earlier and later fruits is extremely important, considering the need of the fresh fruit market, with the increase in the supply of fruits throughout the year, which allows citrus growers, greater economic profitability, with fruits with good characteristics in the off season.
New varieties of Bahia orange trees for table citrus
Keywords: Citrus sinensis; Laranja de umbigo; Ratio; Produtividade; Productivity; Oranges; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA